PENGARUH PENGGUNAAN ALAT PERAGA TERHADAP KEAKTIFAN BELAJAR ANAK SEKOLAH MINGGU USIA 8-13 TAHUN DI HKBP TARUTUNG KOTA RESORT TARUTUNG KOTA TAHUN 2017 - Nurli Simamora (IAKN Tarutung, 2018)
Abstract, This study aims to determine the magnitude of the effect of the use of teaching aids in teaching the Sunday school children to the activity of learning school children at the age of 8-13 years at HKBP Tarutung Kota Resort Tarutung Kota in 2017. This research is a correlational research using Inferential Descriptive Statistics technique, Population is all school children at the age of 8-13 years old in church HKBP Tarutung Kota Resort Tarutung kota totaling 103 people. Samples taken 30% from 103 people = 31 people.The research hypothesis is: there is a positive and significant influence between the use of props to the learning activity of school children at the age of 8-13 years at HKBP Tarutung Kota Resort Tarutung Kota church in 2017. The result of rxy value analysis = 0,927 rtabel = 0,355 and tcount = 13,310 ttabel = 2.045 indicates that the influence of the use of props with the activity of learning school children Sunday. This study concludes that the use of props influences the learning activity of school children by 85.93%. Keywords: Use of Tools, Activity Learning Sunday School Children.